1 A comparison of direct aspiration vs stent retriever as a first approach ('COMPASS'): a randomized trial. (July 2018) - Siddiqui, A; Mocco, J; Turk, A
Abstract : Background and objective: Stent retriever thrombectomy of large vessel occlusion results in better outcomes than medical therapy alone. A recent European study designed to evaluate superior angiographic outcomes with an aspiration first pass approach failed to show superiority but suggested similar clinical outcomes. COMPASS is designed to evaluate whether patients treated with adirect aspiration first pass (ADAPT) approach have non-inferior functional outcomes to those treated with a stent retriever as first-line (SRFL) approach. Materials and methods: 270 patients were enrolled into this prospective randomized open label, blinded outcome assessment and core lab adjudicated trial. Randomization was 1:1 to treatment with either ADAPT or SRFL thrombectomy. Primary outcome is non-inferiority of clinical outcome at 90d as measured by the percentage of patients achieving mRS of 0–2. Secondary outcomes include angiographic outcome, procedural time, mortality and cost analyses. Results: COMPASS completed enrollment on July 5th, 2017and final Data Lock was completed on October 31st, 2017. Preliminary demographic and presentation-imaging analyses show excellent balance between cohorts. COMPASS has achieved successful collection of 96% of 90 d mRS for enrolled patients and 100% of imaging data. Limited preliminary results were presented at ISC 2018. Complete data results will be made at SNIS. Conclusions: COMPASS is the first prospective randomized open label, blinded outcome assessment and core lab adjudicated trial of patients treated with either ADAPT or SRFL approaches specifically designed to determine non-inferiority in functional outcome. Current indicators demonstrate COMPASS has achieved an extremely low loss-to-follow-up rate. These data will provide substantial insight into the appropriateness of aspiration thrombectomy. Disclosures: A. Siddiqui: 1; C; NINDS, NIBIB, NICHHD. 2; C; Cerenovus, Penumbra, Medtronic, Stryker, Corindus, Amnis, Three Rivers, Cerebrotech, Rebound, Abbott, Guidepoint, Gore, Vastrax. 4; C; Imperative, Synchron, Claret, Reist, Cardinal, Blink TBI, Endostream, Serenity, NTI, Viseon, Neurvana, Cerebrotech. 5; C; University at Buffalo, Jacobs Institute. J. Mocco: 1; C; Stryker, Penumbra, Medtronic. 2; C; Rebound, Viseon, Cerebrotech, Endostream, Vastrax. 4; C; Cerebrotech, Imperative, Endostream, Apama, Rebound, Viseon, Neurvana, Cardinal Consulting, BlinkTBI, Serenity, NTI. 5; C; Mount Sinai School of Medicine. A. Turk: 1; C; Stryker, Microvention, Penumbra, Medtronic, Toshiba, Siemens. 2; C; Medtronic, Endostream, Penumbra, Siemens, Vastrax. 4; C; Cerebrotech, Imperative, Endostream, Apama, Rebound, Viseon, Neurvana, Cardinal Consulting, BlinkTBI, Serenity, NTI. 5; C; Medical University of South Carolina.